Step Forward To Inculcate The Knowledge And Practice Of Nutritional Course In Undergraduate Medical Curriculum - Rehana Rehman; Rabiya Ali; Fatima Syed; Rakhshaan Khan (Journal of Bahria University Medical and Dental College)
World Health Organization has recognized the importance of nutrition as an indicator in the Millennium Development Goal (MDG) focusing on the reduction of maternal and under-5-years mortality, especially in the developing countries1. Maternal dietary micronutrient intake is associated with neonatal anthropometry even in women not at risk of malnutrition hence further research is necessary to determine optimal micronutrient intake in all pregnant women with different body mass indices2. Appropriate information regarding nutrition promotes healthy eating3. Poor or deficient knowledge about health and nutrition on the part of health professionals is reflected in lack of identification of risk factors for nutritional deficiency diseases. This also plays an important role in insufficient use of dietary component while managing patients recovering from illness, leading to increased morbidity and mortality4